2018
DOI: 10.1186/s40463-018-0285-8
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between gonial angle and dynamic tongue collapse in children with snoring/sleep disordered breathing – an exploratory pilot study

Abstract: BackgroundDrug induced sleep endoscopy (DISE) is hoped to identify reasons of failure of adenotonsillectomy (AT) in treating pediatric sleep disordered breathing (SDB). Maxillomandibular disproportion has been studied as another association which may explain alternative pathogenesis of SDB. We aimed to explore the relation between the size of the gonial angle and inclination of the epiglottis measured from cone beam CT (CBCT) and tongue base collapse based on DISE in children with SDB.MethodA retrospective cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Contrary to our hypothesis, however, more severely obtuse gonial angles were found to be negatively correlated with markers of perioperative airway dysfunction. Studies in non-TCS patients have found gonial angle to be positively correlated with tongue-based collapse in patients with sleep disordered breathing, 24 and risk of tracheostomy requirement in Robin sequence 25 . However, the data are less clear in TCS.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to our hypothesis, however, more severely obtuse gonial angles were found to be negatively correlated with markers of perioperative airway dysfunction. Studies in non-TCS patients have found gonial angle to be positively correlated with tongue-based collapse in patients with sleep disordered breathing, 24 and risk of tracheostomy requirement in Robin sequence 25 . However, the data are less clear in TCS.…”
Section: Discussionmentioning
confidence: 99%
“…It is related to aesthetic, sleep disorders, orthodontics, risk of angle fracture, and in forensics. 8 …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has been reported that it is controversial whether there are gender and age differences in the gonial angle values [2,17]. There are also studies in the literature investigating the relation of the gonial angle with the dental status [5,7,9,20], the postoperative stability in the treatment of mandibular prognathism [29], the dynamic tongue collapse in children with snoring [30], the course of the inferior alveolar canal [28], osteoporosis among postmenopausal women [31], location of lingula [32] and different skeletal malocclusion types [33]. In these studies, various methods such as cone-beam computed tomography (CBCT) [1], multidetector computed tomography (MDCT) [8], panoramic radiography [2,6,10,[12][13][14][15][19][20][21][22][23]26], cephalogram [5,16], both panoramic radiography and lateral cephalogram [25,27], both direct anthropometry and lateral cephalometry [24], and both CBCT and direct measurement of the dry bones [28] were used.…”
Section: Introductionmentioning
confidence: 99%